Validation of Curriculum Design Information System Model - Thong Chee Ling; Yusmadi Yah Jusoh; Rusli Abdullah; Nor Hayati Alwi (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Information system (IS) is important to institution of higher learning (IHL) especially in the domain of curriculum design. Without the support of IS, curriculum design in IHL is time-consuming, error-prone and much effort need to put in by curriculum designers. Although there are numerous IS developed in curriculum design domain for the past few years, there is still lack of specific IS curriculum design model found in IHL.  This study aims to propose an IS model which provide guidance during curriculum design process. Model validation phase begin with development of prototype which explains the process of creating a prototype according to the proposed model. The study collected 80 responses from the survey and the study resulted that the IS model is useful and able to reduce time, error and effort during curriculum design process.